Developmental pathways of early numerical skills during the preschool to school transition. (October 2021) - Cahoon, Abbie; Gilmore, Camilla; Simms, Victoria
Abstract: Most longitudinal evidence explores the average level of development, suggesting that the relationships between a limited number of variables applies to all learners in the same way. This is the first longitudinal study that investigates multiple component numeric skills within a preschool population using a person-centered approach (i.e., a latent transition analysis), thus allowing for an investigation of different subgroup learning pathways of mathematical skills over time. 128 children aged 43–54 months (at Time 1) were tracked at three time points over 8 months encompassing the transition from preschool through to their first year of primary education. Findings suggest that there are five developmental pathways of mathematical learning with some groups of children making more rapid progress on entry to school than other groups. Those children in the low number skill pathway have a lower rate of growth than more advanced pathways, possibly due to a lack of understanding in cardinality. Findings highlighted the potential importance of language and working memory abilities on mathematical skills development over time. Highlights: Five developmental pathways of mathematical learning during school transition. Some groups of children making more rapid progress in maths on school entry. Children in low number skill pathways have a lower rate of growth. Lower rate of growth possibly due to a lack of cardinal understanding. Language and working memory abilities important for maths development over time.